Development of a simple correlation between bending beam rheometer and thermal stress restrained specimen test low-temperature properties based on a simplified size effect approach. (8th May 2017) - Falchetto, Augusto Cannone; Moon, Ki Hoon; Wistuba, Michael P.
Abstract : In this paper, the possibility of using bending beam rheometer (BBR) experimental results to determine the critical cracking temperature of an asphalt mixture is evaluated. First, thermal stress restrained specimen test (TSRST) together with BBR creep and strength tests is performed on eight asphalt mixtures designed with and without recycled materials. The experimentally determined cracking temperature is initially simply compared and a significant difference is observed between TSRST and BBR values. Based on simple size effect theory, the BBR strength is then converted into the equivalent tensile strength of specimens having the same size of TSRST samples, and the critical cracking temperature is recalculated. The analysis suggests that the TSRST- and BBR-derived cracking temperatures are only in partial agreement.